The Positive Influence of Polyphenols Extracted From Pueraria lobata Root on the Gut Microbiota and Its Antioxidant Capability - Xu, Xiao; Guo, Ying; Chen, Shaoqin; Ma, Wenliang; Xu, Xinlei; Hu, Shuning; Jin, Lifang; Sun, Jianqiu; Mao, Jian; Shen, Chi (Frontiers in Nutrition, 2022)
Pueraria lobata, an edible food and medical, is a rich source of bioactive components. In this study, a polyphenol-rich extract was isolated from P. lobata. Puerarin were identified, and the high antioxidant bioactivity of P. lobata extract evaluated by the methods of DPPH, ABTS and hydroxyl free radicals scavenging ratio. And the IC50 values of DPPH, ABTS and hydroxyl radical scavenging activities were 50.8, 13.9 and 100.4 g/mL, respectively. Then, the P. lobata extract was administered to C57Bl/6J mice and confirmed to have a superior effect on enhancing the antioxidant status including improving superoxide dismutase activity, glutathione peroxidase peroxide activity, total antioxidant capacity activity and malondialdehyde contents in vivo. Furthermore, P. lobata extract had beneficial and prebiotic effects on the composition and structure of gut microbiota. Results showed that P. lobata extract significantly increased the abundance of beneficial bacteria, involving Lactobacillaceae and Bacteroidete，and decreased the abundance of Ruminococcaceae, Prevotellaceae and Burkholderiaceae. Overall, our results provided a basis for using P. lobata extract as a promising and potential functional ingredient for food industry.